Systematic review and meta‐analysis to estimate potential recruitment to dementia intervention studies. (10th October 2013) - Cooper, Claudia; Ketley, Daniel; Livingston, Gill
<x xml:space="preserve">Abstract</x> Objective We investigated the proportion of people with dementia who are eligible for and willing to participate in intervention studies. Methods We systematically reviewed 12 studies fitting predetermined criteria, reporting eligibility or participation rates for dementia intervention trials or intervention studies that sought to increase recruitment. We assessed the study validity using a checklist, reported trial eligibility and participation rates and meta‐analysed these where appropriate. Results In higher quality studies, 26% [95% confidence interval 19–35%] of people with Alzheimer's disease (AD) attending memory clinics or receiving antidementia medication were eligible for industry drug trials, and 43% of eligible people agreed to participate in one study, suggesting 11% of these populations would take part in drug trials if approached. There was replicated, higher quality evidence that younger people, men and those with more education were more likely to be eligible for AD drug trials. No randomised controlled trials have investigated how to increase recruitment to dementia intervention studies. Conclusion One in 10 people with AD or taking donepezil would, according to best available evidence, take part in industry drug trials if approached. We found no data regarding non‐pharmacological intervention or pragmatic drug trial recruitment, but eligibility and participation rates for these studies are probably higher. If international studies are extrapolated to the UK, they suggest the national target of recruiting 10% of people with dementia diagnoses to research may be achieved through a nationwide policy of asking all people with dementia and their carers for consent to be approached for research participation. Copyright © 2013 John Wiley & Sons, Ltd.